Some Personal Experience in Teaching Phonetics for Thai Learners - Fan, Ying (Journal of Sinology (วารสารจีนวิทยา), 2010)
This article describes some general phonetic errors of the Thai learners who are learning Chinese, trying to analyse the reasons of the errors and provide relevant advice to tackle these phonetic problems.